Microsoft encarta 98 deluxe encyclopedia - Microsoft Home (Firm) ([Redmond, WA] : Microsoft Home, 1997)
A multimedia encyclopedia with more than 32,000 articles, plus: several hours of sound, including spoken language; illustrations; video clips and animations; maps; games.
Windows system requirements: multimedia PC with a 486DX/50 MHz or higher microprocessor; Microsoft Windows 95 operating system, or Windows NT version 4.0 or later operating system; 8 MB of RAM for Windows 95 operating system, or 16 MB of RAM for Windows NT workstation; 30 MB of available hard-disk space for Windows 95 or Windows NT; double-speed or faster CD-ROM drive; SVGA 256-color monitor supporting 640x480 or higher resolution; local bus video with 1 MB or more of VRAM; Microsoft Mouse or compatible pointing device; audio board and speakers or headphones. To use Encarta Research organizer, you need 5 more MB RAM ; to use the Yearbook, you need a 9600 baud modem, access to the Microsoft World Wide Web page on the Internet or a user account on the Microsoft Network, to download monthly files, 4 MB of additional hard-disk space, plus 1 MB for each monthly installment.
Keywords: Encyclopedias and dictionaries -- Software; Interactive multimedia; CD-ROMs.